A book review: Contemplation; an Islamic psychospiritual study - Mamat, Ismail; Mukhtar, Mukrimah (Global Academic Exellence, 2017)
This is a book review for English translation entitled “Contemplation; An Islamic Psychospiritual Study”. Its original Arabic edition is Al-Tafakkur min al-Mushahadah ila al-Shuhud. In this work, the author approaches a highly important subject from both an Islamic and modern psychological perspective. He examines the Islamic injunction to contemplate and judge according to the guidance of honest and calm thought. He also examines the meaning and importance of contemplation as a form of worship. Delving into the true meaning and experience of Islamic spirituality, based on a person’s awareness and recognition of his existence and place in creation, the author reveals the limitations and contradictions of the current prevailing school of psychology that deny the existence of the soul and perceive humans as mere machine acting on external stimuli. Combining the rich traditional Islamic wisdom with contemporary knowledge, the author advances a unique approach to the understanding of the human psyche and the self that gives a central position to meditation and contemplation as forms of worship in Islam. This book is addressed to anyone who is interested in the Islamic approach towards the urgency felt by modern societies who are yearning for the rediscovery of the long-forgotten and neglected spiritual aspects of their lives.